Oxidative stress dynamics in Hyalella azteca under sub-chronic exposure to naturally aged polypropylene microplastics - Prado, Caio César Achiles; Queiroz, Lucas Gonçalves; de Paiva, Teresa Cristina Brazil; Pompêo, Marcelo; Ando, Rômulo; Rani-Borges, Bárbara (Aquatic toxicology, 2025)
•The natural process of photoaging altered the structure of polypropylene particles.•Aged plastic polymers are more toxic to non-target organisms.•Microplastics represent serious risks to organisms at the base of the food chain.•Sublethal concentrations showed increased oxidative stress levels after 14 days.•Microplastic also act as carriers for other contaminants, intensifying their effects. Microplastics (MPs) pollution has revealed a serious environmental issue, demonstrating chronic consequences for the affected environments and organisms. Although these plastic particles, pristine and aged, can circulate in different environmental matrices, their actual impacts on aquatic ecosystems are still under investigation. Here, we studied the toxicity of naturally aged secondary polypropylene (PP) MPs after constant exposure to ultraviolet radiation (26 µm) to the freshwater amphipod Hyalella azteca. The concentrations tested were 135, 1350, and 13,500 items/L. H. azteca was investigated for mortality and changes in enzyme markers after 7 and 14 days of exposure followed by a further 7 days of depuration. The results show that mortality was only significant at the highest concentration tested. The concentration of 13,500 items induced oxidative stress after 7 days of exposure only at the MDA levels and CAT activity, while the concentrations of 1350 and 13,500 items/L induced oxidative stress in all tested markers (SOD, CAT, GST and MDA after 14 days. After 7 days of depuration, the levels of biochemical damage were reduced, demonstrating the ability of the species to recover as they are isolated from this pollutant.